Pelatihan Public Speaking Untuk Peningkatan Kepercayaan Diri dan Kompetensi Komunikasi Pada Remaja Penyintas Thalassemia di Kota Sukabumi - Andriani, Ria; Yani, Windri; Destriani, Siti Haniva (Jurnal Surya, 2023)
Thalassemia is a hereditary disease that has experienced blood disorders since toddlers. The main cause is that red blood cells (hemoglobin) are destroyed so quickly that the age of blood cells becomes shorter and the body will experience a lack of blood, mainly located in West Java. The results of pre-research found through partners revealed that increased self-confidence is the main need for children and adolescents with thalassemia. The inferiority complex and health of children and adolescents with thalassemia pressure them to engage in activities and socialize with the environment. One of the confidence needed is the ability to speak publicly. The ability to express opinions and the ability to speak confidently in public is a need for adolescents with thalassemia at POPTI Sukabumi City, West Java. Based on the presentation in the background, this training aims to increase Confidence in Public speaking for Adolescents with Thalassemia (Thaller) at POPTI (Indonesian Association of Parents with Thalassemia) Sukabumi City, West Java. The implementation method is carried out using the lecture and discussion method. The results of this activity ran smoothly and provided an improvement in the participants' abilities regarding tips that can be determined in the implementation of public speaking. Further activities can be carried out by producing scientific research related to this topic and holding advanced training on public speaking.